THE DEVELOPMENT OF THE HUMANISTIC OUTLOOK OF YOUNGER SCHOOL STUDENTS OF A GENERAL EDUCATION SCHOOL IN EXTRA-SCHOOL ACTIVITIES - Klepar, Maria; Potapchuk, Tetyana; Chinchoy, Alexander; Nych, Oksana (Mountain School of Ukrainian Carpaty, 2022)
In this article, we consider the development of the humanistic worldview of younger schoolchildren in extracurricular activities as a set of basic principles: historical and cultural orientation of upbringing and education, which involves the organization of the educational process based on the history and culture of the peoples living in the region, the country; integration of educational disciplines (mastery of art in unity with the study of songs, music, traditions, rituals, etc.); identification and self-actualization of the individual, based on the introduction of knowledge about man and society into the content of the development of humanistic worldview education; harmonization of interethnic relations. We note that this direction of education is able not only to take into account the interests of national cultures and regional cultural traditions, but also the needs of the individual in national and cultural self-identification, the development of the worldview positions of the individual. Therefore, at the current stage, we consider the development of a humanistic worldview as a way to return lost spiritual values, moral and aesthetic norms of behavior, interpersonal relations, family and everyday life. In our opinion, it is humanistic, ethno-cultural education that can help students master the culture of their people (the culture of consumption, the culture of communication, the culture of knowledge, the culture of work), develops a worldview, makes it possible to organize artistic and creative activities, focusing on the national uniqueness of the region. In determining the place and role of humanistic worldview education in out-of-school educational institutions, we consider it as a method that strengthens the effectiveness of education through the introduction of the means of national culture, which will help direct the modern educational and educational process to the formation of ethnic self-awareness, the development of understanding of the role of one's people in world culture. Analyzing the means of national culture used in folk pedagogy, we established that the educational potential of national culture was aimed at forming humanistic, worldviews in children. moral qualities of the individual, a sense of national self-awareness, patriotism, development of creative abilities. Keywords: educational process, humanistic outlook, extracurricular activities, younger schoolchildren, group work.